THE STATE OF BLOOD INDICES IN THE FOUNDRY WORKERS - Pylypenko, N.O.; Nikolenko, E.Ya.; Vovk, K.V.; Reznichenko, O.G.; Kratenko, G.S.; Gridnieva, S.V.; Martynenko, M.V.; Pilipenko, V.V. (World of Medicine and Biology, 2021)
The study of hematological parameters of 42 healthy people who have been working for more than ten years under the influence of dust-forming factors of production environment, among which silicon dioxide dominates, revealed: redistribution of white blood cell percentage; changes in erythrocyte membrane permeability; reduced blood clotting time; erythrocyte sedimentation rate; significant differences compared with control values of integral indices. Such changes are likely to have an adaptive focus, however – with continued contact of the subjects with the harmful factor, such changes can become markers of the development of disorders of innate immunity, with a subsequent risk of occupational chronic bronchopulmonary diseases.